Model Kecerdasan Spiritual Pada Kedisiplinan Santri Di Pondok Pesantren Hidayatul Islamiyah Desa Sumber Agung, Kemiling, Bandar Lampung - Muslih, Muslih; Junilia, Elsy; Perdana, Andre Pebrian (Universitas Sang Bumi Ruwa Jurai, 2024)
The phenomenon in the field shows cases of crime and violations of the law in Islamic boarding schools in recent years such as the case of the Al-Hanifiah Islamic Boarding School in Kediri, the Hidayatul Hikmah Alkahfi Islamic Boarding School in Semarang, that there are still many students committing crimes and breaking the rules. Especially the Hidayatul Islamiyah Islamic Boarding School in Lampung, many students violate the rules in terms of discipline. The purpose of this study is to test empirically normatively to see how the analysis of the rules for organizing Islamic boarding schools regarding student discipline and how the model of spiritual intelligence is in student discipline at the Hidayatul Islamiyah Islamic Boarding School in Sumber Agung Village, Kemiling Bandar Lampung.The method uses an empirical normative approach with a study of the legislation on organizing Islamic boarding schools and uses research variables of spiritual intelligence and discipline. The data collection method uses a study of the legislation on organizing Islamic boarding schools and quantitative (questionnaires) supported by interviews. Research results Analysis of the rules for organizing Islamic Boarding Schools regarding the discipline of students at the Hidayatul Islamiyah Islamic Boarding School in Bandar Lampung The first point is the existence of rules in the Islamic Boarding School regulations Number 34 of 2024, the second point is the punishment for undisciplined students which is given preventively and repressively, the third point is that if there are students who are disciplined, there are awards, the fourth point is the consistency of student discipline which still has several obstacles including the lack of awareness of students towards the rules, lack of supervision from the management and some students consider the application of punishment from the management to be unfair, while the model of spiritual intelligence in the discipline of students at the Hidayatul Islamiyah Islamic Boarding School in Sumber Agung Village, Kemiling District, Bandar Lampung, the results of statistical calculations are the r-xy value of 0.428 with p 0.428 with p 0.018 where p 0.05 means that there is a relationship between the spiritual intelligence model and discipline in students, so that the higher the spiritual intelligence of students, the higher the discipline of students, with an influence of 42.8%.